Pengaruh demonstrasi penggunaan buku pop up sebagai media pembelajaran terhadap motivasi dan penguasaan konsep siswa pada materi sistem endokrin - Nurhanifah, Nada; Hamdiyati, Yanti; Sanjaya, Yayan (Assimilation: Indonesian Journal of Biology Education, 2020)
This research was conducted to determine the increase in students' mastery of the endocrine system material and learning motivation after using learning media in the form of pop up books by demonstration methode because this learning is carried out in the midst of a pandemic that requires students to learn from home. The method that used in this research was experimental research using quasi-experimental research involving two classes, each consisting of 36 students of class XI Science. Determination of the sample was done by using purposive sampling technique. The instrument in this study consisted of tests containing a matter of mastery of the concept of multiple choice forms, and nontest namely the ARCS learning motivation questionnaire and student response questionnaire. Analysis of research results using statistical tests with the help of SPSS to see differences in the results of the initial test and final test, and N-gain to see an increase in mastery of concepts. The results showed that the initial and final test scores had significant differences (âº = 0.05). Reinforcement of concepts in the experimental class increases with the high category (g = 0.806), while the control class increases in the moderate category (g = 0.656). ARCS (Attention, Relevance, Confidence, Satisfaction) are in the high category. Meanwhile, questionnaire analysis showed higher student responses to learning.